(untitled) (REMUNOM, 2023)
Cancer is a disease that affects millions of people every year, and many of them are children. Every 3 minutes a child dies from cancer and every year more than 400.000 people aged 0 to 19 are affected by the disease. Unlike cancers in adults that can be prevented, the causes of most childhood cancers are unknown, they are more aggressive and develop faster, however, the response to treatment is better and the chance of cure is greater. Considering the need for a pharmacist, it is very important not only in the preparation of antineoplastic drugs, but also in the areas of pharmacovigilance, studies, interpretation of laboratory tests and pharmaceutical care and assistance.